A multi-species bait for Chagas disease vectors. - Theo Mota; Ana C R Vitta; Alicia N Lorenzo-Figueiras; Carla P Barezani; Carlos L Zani; Claudio R Lazzari; Liléia Diotaiuti; Lynne Jeffares; Björn Bohman; Marcelo G Lorenzo (PLoS Neglected Tropical Diseases)
Background Triatomine bugs are the insect vectors of Trypanosoma cruzi, the etiological agent of Chagas disease. These insects are known to aggregate inside shelters during daylight hours and it has been demonstrated that within shelters, the aggregation is induced by volatiles emitted from bug feces. These signals promote inter-species aggregation among most species studied, but the chemical composition is unknown. Methodology/principal findings In the present work, feces from larvae of the three species were obtained and volatile compounds were identified by solid phase microextraction-gas chromatography-mass spectrometry (SPME-GC-MS). We identified five compounds, all present in feces of all of the three species: Triatoma infestans, Panstrongylus megistus and Triatoma brasiliensis. These substances were tested for attractivity and ability to recruit insects into shelters. Behaviorally active doses of the five substances were obtained for all three triatomine species. The bugs were significantly attracted to shelters baited with blends of 160 ng or 1.6 µg of each substance. Conclusions/significance Common compounds were found in the feces of vectors of Chagas disease that actively recruited insects into shelters, which suggests that this blend of compounds could be used for the development of baits for early detection of reinfestation with triatomine bugs.